Formal methods : 22nd International Symposium, FM 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 15-17, 2018, Proceedings /: 22nd International Symposium, FM 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 15-17, 2018, Proceedings. (2018) - Unknown
No abstract available